Acoustic and Clinical Data Analysis of Vocal Recordings - Carreiro-Martins, Pedro (2024)
Funding Information: The present publication was funded by Funda\u00E7\u00E3o Ci\u00EAncia e Tecnologia, IP national support through CHRC (UIDP/04923/2020). The project \u201COSCAR\u2014vOice Screening of CoronA viRus\u201D (POCI-01-02B7-FEDER-051277) leading to this work is co-financed by ERDF-European Regional Fund through the Operational Program for Competitiveness and Internationalization, and by LISBOA 2020\u2014Regional Operational Program for Lisbon and Vale do Tejo. Publisher Copyright: © 2024 by the authors.